ASSESSMENT OF AIR TEMPERATURE CHANGE THROUGH PERIODS UNDER CLIMATE CHANGE (In the example of Samarkand region) (Scientific journal of the Fergana State University, 2024)
In the article, based on meteorological calculations and mathematical statistical methods, the current climate change is discussed in the basic (1961-1990) meteorological stations located in Samarkand region (Samarkand, Dahbed, Payshanba, Nurabad, Koshrabad) and the current (1991-2020) climatic periods analyzed changes in air temperature. The results of the analysis showed that the average air temperature has increased in the current climatic period at meteorological stations located in the region. The average air temperature has increased by 1,2°C in Samarkand, by 0,9°C in Dahbed, by 0,8°C in Payshanba, and by 0,7°C in Nurabad and Koshrabad.. The highest temperature in terms of stations was transmitted at the Samarkand station. It should be noted here that the station is located in the city. The average air temperature in the region increased by 0,9°C.